Do shapes and dimensions of scleral flap and sclerostomy influence aqueous outflow in trabeculectomy? A finite element simulation approach. Issue 3 (2nd September 2011) - Tse, Kwong Ming; Lee, Heow Pueh; Shabana, Noor; Loon, Seng-Chee; Watson, Peter G; Thean, See Yin Lennard Harold
Abstract : Background/aim: This study aimed to provide an objective assessment of the effects on the aqueous outflow rate of various geometries of the scleral flap and sclerostomy created in trabeculectomy. Method: Computer-based models and simulations of this surgical procedure were used to investigate the relative effects of various shapes and dimensions of scleral flap and sclerostomy on the aqueous outflow. Result: In these computer simulations, increasing scleral flap size was found to be associated with an increase of 48.55% in aqueous egress. In addition, a square scleral flap increased the aqueous drainage by 36.26% compared with a triangular flap of equivalent flap area. Surprisingly, our simulation results showed that a smaller semicircular sclerostomy improved aqueous drainage by up to 33.00%, while a semicircular sclerostomy, compared with a circular sclerostomy, led to a further 6.16% increase in aqueous outflow. Decreasing flap thickness beyond half-thickness caused an additional increase in aqueous outflow. However, clinically the flap should not be thinner than half the thickness of the sclera as this may result in hypotony. Conclusion: These simulations indicate that the optimal flow rate through operation site will be achieved in trabeculectomy using a square scleral flap with a large flap-to-sclerostomy ratio.